ANALISIS TINGKAT PENGANGGURAN TERBUKA (TPT) DI PROVINSI BANTEN PERIODE TAHUN 2015-2024 - Renti R. Sitorus; Yolanda Sagala; Sri Ningsih (Jurnal Riset Multidisiplin Edukasi, 2026)
This study examines the open unemployment rate (TPT) in Banten Province for the period 2015–2024. Unemployment remains a serious problem in Indonesia, including in Banten, known as an industrial area and a buffer zone for the capital city. Data from the Central Statistics Agency (BPS) shows that the TPT in Banten tends to be higher than the national average, with a fluctuating trend. A sharp increase occurred in 2020 due to the COVID-19 pandemic, but after that the unemployment rate gradually decreased until 2024. The main factors influencing the high unemployment rate in Banten include the imbalance between the workforce and jobs, the mismatch between workforce skills and industry needs, high urbanization, and uneven quality of education. The conclusion of this analysis is that although employment conditions in Banten have shown improvement, structural challenges still need to be addressed. Therefore, the government is advised to increase job creation through investment, development of MSMEs and the creative economy, and strengthening education and skills training to better prepare the workforce for the demands of the modern job market.